The Influence Of Hair Supplement Advertising (Keanu Agl Version) Towards Pantene Brand Image - Pramudya, Farhan Bintang; Dianita, Inria Angga (eProceedings of Management, 2024)
The development of the advertising industry in globalization era is very diverse, where companies are starting to invite influencers to collaborate in order to build a brand image. This study aims to analyze how much influence Hair Supplement Ads (Keanu AGL Version) have on Pantene's Brand Image. This research was conducted using quantitative methods with descriptive research types. The sampling technique used is probability sampling with simple random sampling technique. Through sample size calculation using the Bernoulli formula, a total of 385 respondents were obtained. Empirical data were collected through questionnaires distribution by Google Form and data were analyzed using a simple linear regression approach. The regression analysis result show that the value of the regression coefficient X or variable is 0.589 meaning that every increase of 1 unit can affect the Pantene brand image. Based on the coefficient of determination result, it shows that 53.3% of the variation in brand image variable can be explained by advertising variable. While the remaining 46.7% (100% - 53.3%) can be explained by other factors outside this research model. This study provides a positive contribution to the marketing literature and practically for Pantene's to strive to improve brand image through advertising strategies. Keywords-advertising, brand image, Pantene